Assays for cytokines and cytokine assay standardization - Whiteside, Theresa (Henry Stewart Talks, 2011)
The importance of measuring cytokines, The types of cytokine assays available, Examples of most widely used cytokine assays, Principles of ELISA and ELISPOT, How to select the right cytokine assay, Multiplex analyses and cytokine profiling, Principles of QA/QC for cytokine assays, Data analysis and pitfalls
Archived at 2022/01/31